The Error on the Circumstances of Exclusion of the Penalty: Between The Foundations of Penalty and The Exculpatory Organizer Scope of Principle NULLUM CRIMEN - Rusconi, Maximiliano (2015)
Some problems associated with circumstances related errors that operate at level of guilt and errors associated with individual judgment own circumstances or general criminality.